PERILAKU AROGANSI LEGISLATIF DAN SIKAP APATISME MASYARAKAT BAGI PERANCANGAN MODEL JARING ASPIRASI MASYARAKAT YANG EFEKTIF, ADAPTIF, DAN FLEKSIBEL - Sugeng Rusmiwari (REFORMASI, 2011)
Legislative Behavior that prefer be bad or Arrogant are caused by some factors. Those ara affilating, powerful and well achievement. The under average institution ang the apathetic. Society attitude are influenced by cognate aspect and the confiding aspect. The will effect the bad communication pattern or uneffectively, adaptable and flexible. For those need model that can help solving the problem.